Der Platoniker Tauros in der Darstellung des Aulus Gellius - Lakmann, Marie-Luise. (Philosophia Antiqua, 1995)
Aulus Gellius' accounts of his studies in Athens are a major source for the personality of Taurus the Platonic philosopher of the 2nd century A.D. and besides, give important insights into the history of Platonic school of that time. The present work puts together Gellius' reports on the Middle Platonist for the first time and - by its detailed commentary - offers a new understanding of contents, form and methods of his philosophical instructions, of the relationship between teacher and students, and of student life in the 2nd century A.D. in general. By this means numerous topics in ancient philosophy, philology, science, and pedagogics are dealt with. Finally the results thus gained are combined with all remaining literary and epigraphic evidence, so that a lively portrait of Taurus as a philosophical teacher emerges. A collection of testimonies and fragments concerning Taurus' life and work, a comprehensive bibliography, and indices complete the work.